1998
DOI: 10.1055/s-2006-957470
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitory Components fromArtocarpus incisuson Melanin Biosynthesis

Abstract: The inhibitory effects of methanol extracts of heartwood of 23 Papua New Guinean wood species on tyrosinase activity were examined. The extract of Artocarpus incisus showed the strongest tyrosinase inhibitory activity which was equivalent to kojic acid. The extract apparently inhibited melanin biosynthesis of both cultured B16 melanoma cells without any cytotoxicity and in the back of a brown guinea pig without skin irritation. Thus, the potentiality of the extracts of heartwood of A. incisus both as material … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(69 citation statements)
references
References 9 publications
1
68
0
Order By: Relevance
“…Glabridin, an isoflavan derivatives, was isolated from Allamanda cathartica stem as potent tyrosinase inhibitor [40,41]. Artocarbene, chlorophorin, norartocarpanone, and 4-propylresorcinol including 2,4-substituted resorcinol moiety induce high tyrosinase inhibitory activity [42,43]. Catechol moiety of chalcone exhibits tyrosinase inhibitory activity, and it is reported that the catechol chelates with the copper ions, present in the active site of tyrosinase.…”
Section: Melanogenesis Controlling Effect Of Medicinal Plants Extractmentioning
confidence: 99%
“…Glabridin, an isoflavan derivatives, was isolated from Allamanda cathartica stem as potent tyrosinase inhibitor [40,41]. Artocarbene, chlorophorin, norartocarpanone, and 4-propylresorcinol including 2,4-substituted resorcinol moiety induce high tyrosinase inhibitory activity [42,43]. Catechol moiety of chalcone exhibits tyrosinase inhibitory activity, and it is reported that the catechol chelates with the copper ions, present in the active site of tyrosinase.…”
Section: Melanogenesis Controlling Effect Of Medicinal Plants Extractmentioning
confidence: 99%
“…The extracts were assayed by the modified tyrosinase inhibition method previously described (Shimizu et al, 1998). Briefly, 120 µL of 1.66 mM of tyrosine solution in 0.1 M phosphate buffer (pH 6.8), 60 µL of five serial concentrations of the extracts (0.001-10 mg/mL dissolved in methanol and 20% v/v DMSO 1:1) and 60 µL phosphate buffer were mixed in a 96-well plate and incubated at 37° ± 2°C for 60 min.…”
Section: Tyrosinase Inhibition Assaymentioning
confidence: 99%
“…The major one was ethyl (E)-6-(2-phenyl-4-oxo-4H-1-benzopyran-3-yl)propionate (19) while the minor one was identified as the expected acrylaldehyde (18). The reason of this double reactivity is the presence of two different β hydrogens in contrast with the previous terminal alkenes having only one β hydrogen.…”
Section: Resultsmentioning
confidence: 99%